Action research-driven professional development: Developing transformational health care managers and creating learning organisations - Wolvaardt, Gustaaf; du Toit, Pieter H (South African Journal of Higher Education, 2016)
The Foundation for Professional Development offers, inter alia, an advanced management development programme for health care managers in the public and private sector, sponsored by the USAID and co-certified by Yale University in the USA. The focus is on professional development and transformational leadership. Authentic learning opportunities are created that focus on deep learning in the work context. Portfolio assessment is used. A developmental portfolio is compiled by the health care managers enrolled in the programme. The developmental process is underpinned by the principles of action research. Managers are self-empowered to take responsibility for investigating the transformation of their management practice as a measure of self-driven quality assurance. In most cases the action research process becomes educational to both the manager and his/her colleagues participating in the project. In this way a culture of professional organisational learning is created and maintained. This paper reports a number of case studies of health care managers who conducted action research in an array of health-related contexts, covering health science fields such as HIV/AIDS, tuberculosis and capacity building programmes to create learning organisations and community engagement projects. The lessons learnt by the managers regarding the innovative ideas they experimented with in their specific contexts can be transferred to other managers and action research scholars. All these case studies provide evidence of knowledge being created in authentic contexts. These case studies are reported as scholarly endeavour to showcase the empowering and emancipating nature of action research and the contribution it makes to the existing body of knowledge in different fields in which health care managers have to operate. Keywords: Health care managers, learning organisation, action research, professional portfolios, quality assurance.